Economic Value Added and Profitability of Recycled-Bottle Seaweed Buoys in North Kalimantan - Luluk Merlinda Wati (Athallah Publishing globalindo, 2025)
Plastic waste has become a major environmental challenge in coastal and marine areas, including aquaculture regions. In North Kalimantan, seaweed farming relies heavily on plastic buoys, which contribute significantly to plastic pollution due to degradation and improper disposal. This study aims to analyze the value added and profitability of innovative seaweed buoys made from recycled plastic bottles as an alternative approach to plastic waste management in seaweed aquaculture. The research employed a descriptive quantitative approach combined with economic analysis. Data were collected from seaweed farming groups using recycled-bottle buoys through field observations, interviews, and cost–benefit analysis. The value-added analysis was conducted using the Hayami method, while profitability was measured using indicators such as profit margin, benefit–cost ratio, and break-even point. The results indicate that recycled-bottle seaweed buoys generate positive value added and demonstrate higher profitability compared to conventional plastic buoys. In addition, the innovation contributes to reducing plastic waste and lowering production costs for seaweed farmers. These findings suggest that recycled-bottle seaweed buoys are economically viable and environmentally sustainable, offering a practical solution for plastic waste management and sustainable aquaculture development in North Kalimantan.